The Influence of Convenience, Risk, and Security on Usage Decisions of Digital Bank to the People of Surabaya City - Regita Bintari Prameswari; Lia Nirawati (Journal of Social Commerce, 2025)
The increasing use of digital banking applications encourages the need for an in-depth understanding of the factors that influence usage decisions. This study aims to analyze the influence of convenience, risk, and security on the decision to use SeaBank digital banks on the people of Surabaya City. The research method used was quantitative by collecting data using questionnaires to 271 respondents who used the SeaBank application in the Surabaya area. The data analysis technique used multiple linear regression analysis. The results of the study show that simultaneously the variables of convenience, risk, and safety have a significant effect on the decision to use. Partially, convenience, risk, and safety have a significant positive effect on usage decisions. The implications of the findings can be a guideline for digital banking service providers to improve the quality they have. Focusing on these factors is expected to form the basis for the development of more effective strategies in optimizing the user experience in the world of digital banking.